Health Care Network: Maternal perception regarding the quality of care to children with microcephaly - Daniel Batista Conceição dos Santos; Elaine Ferreira da Silva; Sonia Oliveira Lima; Francisco Prado Reis; Cristiane da Costa Cunha Oliveira (Universidade Federal do Rio de Janeiro, 2019)
Abstract Objective: To identify the perception of primary caregivers on the quality of the Health Care Network of children with microcephaly related to congenital infection. Methods: A cross-sectional study carried out from October 2017 to April 2018. Results: The 105 participants assessed the health of their children as reasonable (56.1%). The level of care which got the highest percentage - 57 (54.3%) - of participants' dissatisfaction was of Primary Health Care (p=0.0216). Most of the specialties of secondary health care services were classified as poor/very poor, regarding the quality of the consultation at the secondary level (p<0.05). For the majority - 61 (58%) - of the mothers, regarding this level of attention, the items waiting time and appointment scheduling were evaluated as excellent/good (p<0.05). Conclusion and implications for practice: There is dissatisfaction among mothers considering the quality of services provided by the health care network for children with microcephaly, mainly in primary care. There was easiness in the access to Secondary Care, and little use of Tertiary Care services. It is urgent to elaborate policies that better disseminate humanization and facilitate the accessibility to multiprofessional care for those children.